Oil-water separation composite material and preparation method and application thereof

CN118372539BActive Publication Date: 2026-10-23WUHAN TEXTILE UNIV +2
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410353189.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-26
Publication Date
2026-10-23
Estimated Expiration
2044-03-26

AI Technical Summary

Technical Problem

然而,该方法中的薄膜覆盖及加热至薄膜形成鼓泡的方式并不属于常规织物生产过程的工序,在实际生产过程中需要额外使用特定的装置进行生产,增加了设备的成本,整体制备工序也较为复杂;且该方法提供的油水分离织物的性能及其油水分离速率仍有待提高

Benefits of technology

[0026]1、本发明提供了一种油水分离复合材料的制备方法,通过对高性能纤维毡进行亲油疏水或亲水疏油处理,并在处理后的高性能纤维毡的上下表面分别复合超亲水功能织物和疏油功能织物,形成由上至下依次为超亲水功能织物、处理后的高性能纤维毡、疏油功能织物的三明治复合结构,并使上下表面的织物对高性能纤维毡进行紧密包裹,通过上下挤压物理压缩高性能纤维毡的厚度,使其厚度压缩至原本厚度的50%~70%,并通过封边,使纤维毡厚度维持压缩状态。在此基础上,使用涤纶布制备的超亲水功能织物和疏油功能织物由于不易变形,能够持续对纤维毡的压缩,并实现装置稳定性。基于此,当机油与水形成的油水混合物与本发明提供的油水分离复合材料上表面的超亲水功能织物接触时,超亲水功能织物通过芯吸作用快速吸附油水混合物中因重力作用分层后下层的水,从而形成水膜,成为第一层阻拦油的屏障。压缩后的高性能纤维毡相比于常规的未经压缩的厚度较薄的小孔隙纤维毡具有更高的孔隙率和密度,通过纤维交叉形成的小孔隙能够实现对水的物理作用导水,并且,由于超亲水功能织物的阻拦,压缩后的高性能纤维毡还能够加速水的通过。同时,纤维毡能够存储一部分经过纤维毡的水,保持超亲水功能织物的湿润,维持水膜的形成,阻隔机油的通过,从而利用各层的织物结构及其对水、油的亲疏特性之间的协同作用,实现了高效的油水分离。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118372539B_ABST
    Figure CN118372539B_ABST
Patent Text Reader

Abstract

The application provides an oil-water separation composite material and a preparation method and application thereof. The preparation method of the oil-water separation composite material comprises the following steps: performing oleophilic and hydrophobic treatment or hydrophilic and oleophobic treatment on a high-performance fiber felt to obtain a treated high-performance fiber felt; and respectively compositing super-hydrophilic functional fabric and oleophobic functional fabric on the upper surface and the lower surface of the treated high-performance fiber felt, and making the fabric on the upper surface and the lower surface compress the high-performance fiber felt to obtain the oil-water separation composite material. Through the above method, the oil-water separation composite material prepared by the application has a sandwich composite structure, and can realize efficient oil-water separation by utilizing the synergistic effect between the fabric structures of the layers and the affinity and repellency characteristics of the layers to water and oil. Moreover, the oil-water separation composite material has extremely high mechanical properties, high-temperature resistance and corrosion resistance, can adapt to various extreme environments, and the oil-water separation process can be repeatedly performed, so that the oil-water separation composite material can be applied to automobile engines to recycle and reuse engine oil.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of oil-water separation materials technology, and in particular to an oil-water separation composite material, its preparation method, and its application. Background Technology

[0002] In today's era of rapid development in new energy, the development of new energy vehicles can help reduce reliance on fuel and promote industrial upgrading. However, during operation, water vapor or condensation in the environment can easily mix with engine oil, forming a water-oil mixture, which significantly impacts the reusability of the engine oil.

[0003] Conventional oil-water separation primarily achieves separation of the mixture through the hydrolysis of oil. However, this method leads to oil decomposition, thus affecting the reuse of engine oil. Furthermore, due to the high viscosity of engine oil, traditional filtration methods for diesel-water mixtures are difficult to use for separation. How to effectively separate engine oil and water mixtures through filtration for oil recycling remains a pressing problem to be solved.

[0004] In the prior art, patent CN109680502A discloses an oil-water separation fabric, its preparation method, and its application. This patent involves covering both sides of a washed fabric treated with an alkaline reaction solution with a thin film, drying it at temperatures exceeding 100°C until the film forms bubbles, removing it, rinsing it with deionized water until the pH reaches 7, and then drying it. However, the film covering and heating to the point of bubbling in this method are not standard procedures in conventional fabric production. In actual production, specific equipment is required, increasing equipment costs and making the overall preparation process more complex. Furthermore, the performance and oil-water separation rate of the oil-water separation fabric provided by this method still need improvement.

[0005] In view of this, it is necessary to design an improved oil-water separation composite material, its preparation method, and its application to solve the above problems. Summary of the Invention

[0006] To address the shortcomings of the prior art, the present invention aims to provide an oil-water separation composite material, its preparation method, and its application. The present invention involves treating a high-performance fiber felt with oleophilic-hydrophobic or hydrophilic-oleophobic properties, then laminating a superhydrophilic functional fabric and an oleophobic functional fabric onto the upper and lower surfaces of the treated high-performance fiber felt, respectively. The high-performance fiber felt is then compressed using the fabrics on the upper and lower surfaces. By utilizing the synergistic effect between the fabric structure of each layer and its affinity for water and oil, highly efficient oil-water separation is achieved.

[0007] To achieve the above objectives, the present invention provides a method for preparing an oil-water separation composite material, comprising the following steps:

[0008] S1. Perform oleophilic-hydrophobic treatment or hydrophilic-oleophobic treatment on the high-performance fiber felt to obtain the treated high-performance fiber felt.

[0009] S2. A superhydrophilic functional fabric is laminated onto the upper surface of the treated high-performance fiber felt, and an oleophobic functional fabric is laminated onto the lower surface of the treated high-performance fiber felt. The superhydrophilic and oleophobic functional fabrics are then used to compress the high-performance fiber felt to obtain an oil-water separation composite material.

[0010] As a further improvement of the present invention, in step S1, the high-performance fiber felt is formed by needle punching high-performance fibers, wherein the high-performance fibers are one or more selected from glass fiber, quartz fiber, carbon fiber, basalt fiber, aluminosilicate fiber, polyimide fiber, aramid fiber, and polyphenylene sulfide fiber; the basis weight of the high-performance fiber felt is 100 g / m². 2 ~140g / m 2 The thickness is 0.3–30 mm, the fabric width is 5–100 cm, and the porosity is 50%–70%.

[0011] As a further improvement of the present invention, in step S2, the superhydrophilic functional fabric is obtained by hydrophilic treatment of the first fabric; the hydrophilic treatment method includes: immersing the first fabric in a hydrophilic treatment solution for 1-30 minutes, removing it and pressing it 1-5 times under a pressure range of 0.1-0.8 MPa, and then baking the pressed first fabric at 100-200℃ for 1-120 minutes to obtain the superhydrophilic functional fabric; the warp yarn count of the first fabric is 150-1680D, the weft yarn count is 150-1680D, the thickness is 0.1-2 mm, and the weight is 50-900 g / m². 2 .

[0012] As a further improvement of the present invention, in step S2, the oleophobic functional fabric is obtained by treating the second fabric with an oleophobic coating. The oleophobic coating method includes: laying the second fabric flat, uniformly spraying a hydrophilic and oleophobic finishing agent 1-10 times with a spray gun, and spraying at a pressure of 0.05-2 MPa; after spraying, baking the second fabric at 100-200°C for 1-120 minutes to obtain the oleophobic functional fabric; the warp yarn count of the second fabric is 150-1680D, the weft yarn count is 150-1680D, the thickness is 0.1-2 mm, and the weight is 50-900 g / m². 2 .

[0013] As a further improvement of the present invention, in step S1, the method of oleophilic-hydrophobic or hydrophilic-oleophobic treatment includes:

[0014] S11. Prepare a solution of oleophilic and hydrophobic finishing agent or a solution of hydrophilic and oleophobic finishing agent of a predetermined concentration;

[0015] S12. The finishing agent solution prepared in step S11 is loaded into the high-performance fiber felt by impregnation or spraying.

[0016] S13. Baking treatment is performed on the high-performance fiber felt loaded with finishing agent solution.

[0017] As a further improvement of the present invention, in step S11, the oleophilic-hydrophobic finishing agent solution contains a hydrophobic agent and a crosslinking agent; the concentration of the hydrophobic agent is 0.5-30 g / 100 mL, and the concentration of the crosslinking agent is 0.5-10 g / 100 mL;

[0018] The hydrophobic agent includes one or more of the following: modified siloxane treatment agent, 2-methylimidazolium cobalt salt, hexadecyltrimethoxysilane, polydimethylsiloxane, TiO2 nanoparticles, 3-aminopropyltriethoxysilane and polydimethylsiloxane, vinyltriethoxysilane, (3-chloropropyl)triethoxysilane, trifluoroethyl acrylate, trifluoroethyl methacrylate, hexafluorobutyl methacrylate, methacrylate, butyl methacrylate, methacrylamide, isobornyl methacrylate, octadecylamine, triethoxyoctylsilane, dodecyltrimethoxysilane, and hexadecyltrimethoxysilane.

[0019] The crosslinking agent includes one or more of the following: silane coupling agent, toluene diisocyanate, diphenylmethane diisocyanate, naphthalene diisocyanate, terephthalic diisocyanate, dimethylbiphenyl diisocyanate, polymethylene polyphenyl isocyanate, 1,6-hexamethylene diisocyanate, trimethyl-1,6-hexamethylene diisocyanate, isoflurone diisocyanate, 1,4-cyclohexane diisocyanate, dicyclohexylmethane diisocyanate, methylcyclohexyl isocyanate, cyclohexane dimethylene diisocyanate, norbornene dimethylene isocyanate, HDI trimer, and IPDI trimer.

[0020] As a further improvement of the present invention, in step S11, the hydrophilic oleophobic finishing agent solution contains an oleophobic agent, and the concentration of the oleophobic agent in the hydrophilic oleophobic finishing agent solution is 0.5 to 30 g / 100 mL;

[0021] The oleophobic agent includes one or more of the following: fluoroacrylate polymer treatment agent, nano and micron-sized organosilicon filler, diaminosiloxane end-capping agent and hydrolysis product of alkoxysilane, olefinic hydrophilic monomer, hydroxyl-containing fluorinated polyether, fluorocarbon alcohol, hydroxyl silicone oil, octadecyl alcohol, stearyl alcohol, ester wax alcohol, amino-containing fluorinated polyether, aminofluorocarbon, amino silicone oil, octadecylamine, methoxyfluorosilane, ethoxyfluorosilane, propoxyfluorosilane, perfluoroalkyl trichlorosilane, fluoroisocyanate, silicone isocyanate, octadecyl isocyanate, dodecafluoroheptyl methacrylate, and hydroxyethyl methacrylate.

[0022] As a further improvement of the present invention, in step S13, the baking temperature is 100-200°C and the baking time is 1-120 min.

[0023] To achieve the above objectives, the present invention provides an oil-water separation composite material, which is prepared according to the preparation method provided by any of the above technical solutions, comprising a high-performance fiber felt treated with oleophilic-hydrophobic or hydrophilic-oleophobic treatment, a superhydrophilic functional fabric disposed on the upper surface of the high-performance fiber felt, and an oleophobic functional fabric disposed on the lower surface of the high-performance fiber felt.

[0024] This invention also provides the application of the above-mentioned oil-water separation composite material in the field of automotive engines.

[0025] The beneficial effects of this invention are:

[0026] 1. This invention provides a method for preparing an oil-water separation composite material. The method involves treating a high-performance fiber felt with either oleophilic / hydrophobic or hydrophilic / oleophobic properties, and then bonding a superhydrophilic functional fabric and an oleophobic functional fabric to the upper and lower surfaces of the treated high-performance fiber felt, respectively. This forms a sandwich composite structure consisting of a superhydrophilic functional fabric, the treated high-performance fiber felt, and the oleophobic functional fabric, arranged from top to bottom. The upper and lower surface fabrics tightly wrap the high-performance fiber felt, and the thickness of the high-performance fiber felt is physically compressed by compression from top to bottom to 50%–70% of its original thickness. Sealing the edges maintains the compressed thickness. Furthermore, the superhydrophilic and oleophobic functional fabrics made of polyester fabric are not easily deformed, allowing for continuous compression of the fiber felt and ensuring device stability. Therefore, when an oil-water mixture (oil and water) comes into contact with the superhydrophilic functional fabric on the upper surface of the oil-water separation composite material provided by this invention, the superhydrophilic functional fabric rapidly adsorbs the lower layer of water that has separated due to gravity in the oil-water mixture through wicking, thus forming a water film, which becomes the first barrier against oil. Compared to conventional, uncompressed, thinner, small-pore fiber felt, compressed high-performance fiber felt has higher porosity and density. The small pores formed by the interlacing of fibers enable the physical conduction of water. Furthermore, due to the barrier effect of the superhydrophilic functional fabric, the compressed high-performance fiber felt can accelerate water passage. At the same time, the fiber felt can store some of the water passing through it, keeping the superhydrophilic functional fabric moist, maintaining the formation of a water film, and blocking the passage of engine oil. Thus, by utilizing the synergistic effect of the fabric structure of each layer and its affinity and repulsion properties for water and oil, highly efficient oil-water separation is achieved.

[0027] 2. The preparation method of the oil-water separation composite material provided by this invention achieves oil-water separation by treating high-performance fiber felt with oleophilic-hydrophobic or hydrophilic-oleophobic agents, effectively improving oil-water separation efficiency compared to untreated high-performance fiber felt. Furthermore, by selecting and optimizing the treatment method of the high-performance fiber felt and the specific composition of the oleophilic-hydrophobic finishing agent solution and the hydrophilic-oleophobic finishing agent solution, this invention can effectively control the filtration rate of the oil-water separation composite material to meet the needs of different application scenarios.

[0028] 3. The oil-water separation composite material provided by this invention not only achieves efficient filtration of oil-water mixtures but also enables repeated filtration. Furthermore, this oil-water separation composite material possesses extremely high mechanical properties, high-temperature resistance, and corrosion resistance, making it adaptable to various extreme environments. Applying this oil-water separation composite material to automotive engines allows for rapid and effective filtration of the oil-water mixture, filtering out the water while simultaneously blocking the oil for recycling and reuse. This filtration process can be repeated, and even after multiple uses and at least a significant amount of oil has permeated the material, effective water filtration can still be achieved, demonstrating high practical application value. Attached Figure Description

[0029] Figure 1 This is a schematic diagram of the structure of the oil-water separation composite material provided by the present invention.

[0030] Figure 2 This is a schematic diagram of the compression state of the high-performance fiber felt in the oil-water separation composite material provided by the present invention.

[0031] Figure 3 This is a schematic diagram illustrating the application status of the oil-water separation composite material provided by the present invention.

[0032] Figure Labels

[0033] 1. Superhydrophilic functional fabric; 2. High-performance fiber felt; 3. Oleophobic functional fabric; 4. Air inlet; 5. Central column; 6. Liquefaction module; 7. Controllable valve. Detailed Implementation

[0034] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be described in detail below with reference to the accompanying drawings and specific embodiments.

[0035] It should also be noted that, in order to avoid obscuring the present invention with unnecessary details, only the structures and / or processing steps closely related to the present invention are shown in the accompanying drawings, while other details that are not closely related to the present invention are omitted.

[0036] Additionally, it should be noted that the terms “comprising,” “including,” or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such process, method, article, or apparatus.

[0037] This invention provides a method for preparing an oil-water separation composite material, comprising the following steps:

[0038] S1. Perform oleophilic-hydrophobic treatment or hydrophilic-oleophobic treatment on the high-performance fiber felt to obtain the treated high-performance fiber felt.

[0039] S2. A superhydrophilic functional fabric is laminated onto the upper surface of the treated high-performance fiber felt, and an oleophobic functional fabric is laminated onto the lower surface of the treated high-performance fiber felt. The superhydrophilic and oleophobic functional fabrics are then used to compress the high-performance fiber felt to obtain an oil-water separation composite material.

[0040] In step S1, the method of oleophilic-hydrophobic or hydrophilic-oleophobic treatment includes:

[0041] S11. Prepare a solution of oleophilic and hydrophobic finishing agent or a solution of hydrophilic and oleophobic finishing agent of a predetermined concentration;

[0042] S12. The finishing agent solution prepared in step S11 is loaded into the high-performance fiber felt by impregnation or spraying.

[0043] S13. Baking treatment is performed on the high-performance fiber felt loaded with finishing agent solution.

[0044] More specifically, the method of oleophilic-hydrophobic treatment by immersion includes the following steps:

[0045] (1) Impregnate the high-performance fiber felt with a pre-prepared oleophilic and hydrophobic finishing agent solution;

[0046] (2) The high-performance fiber felt impregnated with an oleophilic and hydrophobic finishing agent solution is rolled using a rolling mill; the number of rolling cycles is preferably 1 to 10, more preferably 1; the roll residue is preferably 30% to 90%;

[0047] (3) Bake at 100-200℃ for 1-60 minutes; the preferred baking temperature is 150℃ and the preferred baking time is 3 minutes.

[0048] The method of applying an oleophilic and hydrophobic coating by spraying includes the following steps:

[0049] (1) The pre-prepared oleophilic and hydrophobic finishing agent solution is uniformly sprayed onto the surface of the high-performance fiber felt using a spray gun; the spraying pressure is preferably 0.05 to 2 MPa, more preferably 0.4 MPa;

[0050] (2) Bake at 100-200℃ for 1-60 minutes; the preferred baking temperature is 150℃ and the preferred baking time is 3 minutes.

[0051] In both of the above methods, the oleophilic-hydrophobic finishing agent solution comprises a hydrophobic agent and a crosslinking agent; wherein, the concentration of the hydrophobic agent is preferably 0.5-30 g / 100 mL, more preferably 6 g / 100 mL; and the concentration of the crosslinking agent is preferably 0.5-10 g / 100 mL, more preferably 4 g / 100 mL.

[0052] The hydrophobic agent may be a modified siloxane treatment agent, such as 2-methylimidazolium cobalt salt, hexadecyltrimethoxysilane, polydimethylsiloxane, TiO2 nanoparticles, 3-aminopropyltriethoxysilane and polydimethylsiloxane, vinyltriethoxysilane, (3-chloropropyl)triethoxysilane, trifluoroethyl acrylate, trifluoroethyl methacrylate, hexafluorobutyl methacrylate, methacrylate, butyl methacrylate, methacrylamide, isobornyl methacrylate, octadecylamine, triethoxyoctylsilane, dodecyltrimethoxysilane, and hexadecyltrimethoxysilane. One or more of the following crosslinking agents: silane coupling agent, toluene diisocyanate, diphenylmethane diisocyanate, naphthalene diisocyanate, terephthalic diisocyanate, dimethylbiphenyl diisocyanate, polymethylene polyphenyl isocyanate, 1,6-hexamethylene diisocyanate, trimethyl-1,6-hexamethylene diisocyanate, isoflurone diisocyanate, 1,4-cyclohexane diisocyanate, dicyclohexylmethane diisocyanate, methylcyclohexyl isocyanate, cyclohexane dimethylene diisocyanate, norbornene dimethylene isocyanate, HDI trimer, IPDI trimer.

[0053] More preferably, the hydrophobic agent is polydimethylsiloxane and vinyltriethoxysilane, and the crosslinking agent is toluene diisocyanate, which have better hydrophobic effects compared to other hydrophobic agents and crosslinking agents.

[0054] The method of hydrophilic and oleophobic treatment by immersion includes the following steps:

[0055] (1) Impregnate the high-performance fiber felt with a pre-prepared hydrophilic and oleophobic finishing agent solution;

[0056] (2) A rolling mill is used to roll the high-performance fiber felt impregnated with a hydrophilic and oleophobic finishing agent solution; the number of rolling cycles is preferably 1 to 10, more preferably 1; the rolling mill pressure is preferably 0.05 to 1.5 MPa; the roll-out rate is preferably 30% to 90%, more preferably 65%;

[0057] (3) Bake at 100-200℃ for 1-60 minutes; the preferred baking temperature is 140℃ and the preferred baking time is 3 minutes.

[0058] The method of applying hydrophilic and oleophobic coating by spraying includes the following steps:

[0059] (1) The pre-prepared hydrophilic and oleophobic finishing agent solution is uniformly sprayed onto the surface of the high-performance fiber felt using a spray gun; the spraying air pressure is preferably 0.05 to 2 MPa, more preferably 0.4 MPa;

[0060] (2) Bake at 100-200℃ for 1-60 minutes; the preferred baking temperature is 140℃ and the preferred baking time is 3 minutes.

[0061] In both of the above methods, the hydrophilic-oleophobic finishing agent solution contains an oleophobic agent. The concentration of the oleophobic agent in the hydrophilic-oleophobic finishing agent solution is preferably 0.5–30 g / 100 mL, more preferably 6 g / 100 mL.

[0062] The oleophobic agent may be one or more of the following: fluoroacrylate polymer treatment agent, nano- and micron-sized organosilicon filler, diaminosiloxane end-capping agent and hydrolysis product of alkoxysilane, olefinic hydrophilic monomer, hydroxyl-containing fluorinated polyether, fluorocarbon alcohol, hydroxyl silicone oil, octadecyl alcohol, stearyl alcohol, ester wax alcohol, amino-containing fluorinated polyether, amino fluorocarbon, amino silicone oil, octadecylamine, methoxyfluorosilane, ethoxyfluorosilane, propoxyfluorosilane, perfluoroalkyl trichlorosilane, fluoroisocyanate, silicone isocyanate, octadecyl isocyanate, dodecafluoroheptyl methacrylate, and hydroxyethyl methacrylate.

[0063] More preferably, the oleophobic agent is propoxyfluorosilane or perfluoroalkyl trichlorosilane, which has better hydrophilic and oleophobic effects compared to other oleophobic agents.

[0064] In step S1, the high-performance fiber felt is formed by needle punching high-performance fibers, wherein the high-performance fibers are one or more selected from glass fiber, quartz fiber, carbon fiber, basalt fiber, aluminosilicate fiber, polyimide fiber, aramid fiber, and polyphenylene sulfide fiber; the basis weight of the high-performance fiber felt is 100 g / m². 2 ~140g / m 2 The thickness is 0.3–30 mm, the fabric width is 5–100 cm, and the porosity is 50%–70%.

[0065] In step S2, the superhydrophilic functional fabric is obtained by hydrophilic treatment of the first fabric. The hydrophilic treatment method includes: immersing the first fabric in a hydrophilic treatment solution for 1-30 minutes, removing it and then pressing it 1-5 times under a pressure range of 0.1-0.8 MPa, and then baking the pressed first fabric at 100-200℃ for 1-120 minutes to obtain the superhydrophilic functional fabric. The warp yarn count of the first fabric is 150-1680D, the weft yarn count is 150-1680D, the thickness is 0.1-2 mm, and the weight is 50-900 g / m². 2 The hydrophilic treatment solution comprises vinyltriethoxysilane and toluene diisocyanate as a crosslinking agent, wherein the concentration of vinyltriethoxysilane is preferably 6 g / 100 mL and the concentration of toluene diisocyanate is preferably 4 g / 100 mL.

[0066] The oleophobic functional fabric is obtained by treating a second fabric with an oleophobic coating. The oleophobic coating method includes: laying the second fabric flat and uniformly spraying a hydrophilic and oleophobic finishing agent 1-10 times using a spray gun at a spray pressure of 0.05-2 MPa; after spraying, baking the second fabric at 100-200℃ for 1-120 minutes to obtain the oleophobic functional fabric; the second fabric has a warp yarn count of 150-1680D, a weft yarn count of 150-1680D, a thickness of 0.1-2 mm, and a weight of 50-900 g / m². 2 The hydrophilic-oleophobic finishing solution contains propoxyfluorosilane, and the preferred concentration of propoxyfluorosilane in the hydrophilic-oleophobic finishing solution is 6 g / 100 mL.

[0067] The first and second fabrics can be any of the following: polyester fabric, wool fabric, nylon fabric, cotton fabric, polyester-cotton fabric, nylon-cotton fabric, polypropylene fabric, aramid fabric, vinylon fabric, acrylic fabric, chlorofiber fabric, polyimide fabric, ultra-high molecular weight polyethylene fabric, basalt fiber fabric, carbon fiber fabric, glass fiber fabric, quartz fiber fabric, ceramic fiber, etc. (including blended fabrics of different fibers). Polyester fabric is more preferred because it is less prone to deformation, can continuously compress the high-performance fiber felt, and has high stability.

[0068] In step S2, the superhydrophilic functional fabric, the treated high-performance fiber felt, and the oleophobic functional fabric are preferably bonded together by physical compression to compress the thickness of the high-performance fiber felt to 50% to 70% of its initial thickness.

[0069] This invention also provides an oil-water separation composite material, which is prepared according to the preparation method provided in the above technical solution and has a sandwich structure, as shown in the schematic diagram below. Figure 1As shown, it includes a high-performance fiber felt 2 treated with oleophilic-hydrophobic or hydrophilic-oleophobic treatment, a superhydrophilic functional fabric 1 disposed on the upper surface of the high-performance fiber felt, and an oleophobic functional fabric 3 disposed on the lower surface of the high-performance fiber felt.

[0070] The high-performance fiber felt is compressed by the superhydrophilic and oleophobic functional fabrics, as illustrated in the diagram below. Figure 2 As shown.

[0071] This oil-water separation composite material can be applied in automobile engines, and its application status is illustrated in the diagram below. Figure 3 As shown. By Figure 3 As can be seen, the two sides of the central pillar 5 below the air intake 4 are liquefaction modules 6. The oil-water separation composite material provided by this invention is set as an oil-water separation component below the liquefaction module 6 in the automobile engine. The gaseous oil-water mixture entering through the air intake 4 is liquefied by the liquefaction module 6 and discharged to the surface of the oil-water separation composite material. The water in the oil-water mixture is first absorbed by the superhydrophilic functional fabric 1. The small amount of oil mixed in is further separated by the high-performance fiber felt 2. Finally, the oil is further blocked by the oleophobic functional fabric 3, so that the separated water is discharged from the bottom through the controllable valve 7, thereby achieving efficient oil-water separation.

[0072] The oil-water separation composite material, its preparation method, and its application provided by the present invention will be described in detail below with reference to specific embodiments.

[0073] Example 1

[0074] This embodiment provides a method for preparing an oil-water separation composite material, including the following steps:

[0075] S1. The high-performance fiber felt is subjected to oleophilic and hydrophobic treatment to obtain the treated high-performance fiber felt.

[0076] In this embodiment, the high-performance fiber felt used is basalt fiber needle-punched felt with a basis weight of 100 g / m². 2 It has a thickness of 8mm, a width of 140cm, and a porosity of 70%.

[0077] In this embodiment, the oleophilic-hydrophobic treatment specifically includes the following steps:

[0078] S11. Mix 6g of the hydrophobic agent vinyltriethoxysilane and polydimethylsiloxane mixture with 4g of the crosslinking agent toluene diisocyanate and dissolve in 100mL of deionized water to prepare an oleophilic-hydrophobic finishing agent solution; in this oleophilic-hydrophobic finishing agent solution, the concentration of the hydrophobic agent is 6g / 100mL and the concentration of the crosslinking agent is 4g / 100mL.

[0079] S12. The high-performance fiber felt is immersed in the above-mentioned oleophilic and hydrophobic finishing agent solution, and rolled once with a rolling mill, controlling the roll residue rate to 65%, to obtain a high-performance fiber felt loaded with the oleophilic and hydrophobic finishing agent solution.

[0080] S13. The high-performance fiber felt loaded with an oleophilic and hydrophobic finishing agent solution is baked at a temperature of 150°C for 3 minutes.

[0081] S2. A superhydrophilic functional fabric is laminated onto the upper surface of the treated high-performance fiber felt, and an oleophobic functional fabric is laminated onto the lower surface of the treated high-performance fiber felt. The lamination is performed by physical compression bonding, so that the superhydrophilic and oleophobic functional fabrics compress the thickness of the high-performance fiber felt to 60% of its initial thickness, thereby obtaining an oil-water separation composite material.

[0082] The superhydrophilic functional fabric is obtained by hydrophilic treatment of a first fabric. The hydrophilic treatment method includes: immersing the first fabric in a hydrophilic treatment solution (6 g / 100 mL of vinyltriethoxysilane and 4 g / 100 mL of toluene diisocyanate) for 5 minutes; removing it and then rolling it once under a pressure of 0.3 MPa; finally, baking the rolled first fabric at 170°C for 10 minutes to obtain the superhydrophilic functional fabric. The first fabric is a polyester woven fabric with a warp yarn count of 450D, a weft yarn count of 450D, a thickness of 0.8 mm, and a weight of 500 g / m². 2 .

[0083] The oleophobic functional fabric is obtained by treating a second fabric with an oleophobic coating. The oleophobic treatment method includes: laying the second fabric flat, spraying it three times with a hydrophilic oleophobic finishing agent oleophobic treatment solution (6g / 100mL propoxyfluorosilane solution) using a spray gun at a spray pressure of 0.4MPa; after spraying, baking the second fabric at 140℃ for 3 minutes to obtain the oleophobic functional fabric. The second fabric is a polyester woven fabric with a warp yarn count of 450D, a weft yarn count of 450D, a thickness of 0.8mm, and a weight of 500g / m². 2 To test the oil-water separation effect of the oil-water separation composite material provided in this embodiment, engine oil and water were mixed at a volume ratio of 70:30 to form an oil-water mixture, which was then filtered using the oil-water separation composite material provided in this embodiment. The results showed that when separating the oil-water mixture using the oil-water separation composite material provided in this embodiment, the separation rate was approximately 100 mL / min, and the oil-water separation efficiency was approximately 99%.

[0084] Example 2

[0085] This embodiment provides a method for preparing an oil-water separation composite material. Compared with Embodiment 1, the only difference is that the oleophilic-hydrophobic treatment in step S1 is changed to a hydrophilic-oleophobic treatment. The remaining steps are the same as in Embodiment 1 and will not be repeated here.

[0086] In this embodiment, the hydrophilic and oleophobic treatment specifically includes the following steps:

[0087] S11. Dissolve 6g of the oleophobic agent propoxyfluorosilane in 100mL of deionized water to prepare a hydrophilic oleophobic finishing agent solution; the concentration of the oleophobic agent in the hydrophilic oleophobic finishing agent solution is 6g / 100mL.

[0088] S12. The high-performance fiber felt is impregnated in the above hydrophilic and oleophobic finishing agent solution, and rolled once with a rolling mill, with the roll residue rate controlled at 65%, to obtain a high-performance fiber felt loaded with hydrophilic and oleophobic finishing agent solution.

[0089] S13. The high-performance fiber felt loaded with hydrophilic and oleophobic finishing agent solution is baked at a temperature of 140°C for 3 minutes.

[0090] When using the oil-water separation composite material provided in this embodiment to separate a mixture of engine oil and water, the separation rate is approximately 50 mL / min, and the oil-water separation efficiency is approximately 99%.

[0091] Comparative Example 1

[0092] This comparative example provides a method for preparing an oil-water separation composite material. Compared with Example 1, the difference is that the high-performance fiber felt is not treated. Instead, polyester fabric is directly laminated onto the upper and lower surfaces of the high-performance fiber felt in accordance with step S2. The specifications of the high-performance fiber felt and the polyester fabric and their lamination method are the same as those in Example 1, and will not be repeated here.

[0093] When using the oil-water separation composite material provided in this comparative example to separate a mixture of engine oil and water, the separation rate is approximately 10 mL / min, and the oil-water separation efficiency is approximately 99%.

[0094] Comparing Examples 1 and 2 with Comparative Example 1, it can be seen that the treatment method of the high-performance fiber felt does not affect its oil-water separation efficiency, but it does affect the separation rate. This is mainly because: the oleophilic-hydrophobic treatment in Example 1, compared with the hydrophilic-oleophobic treatment in Example 2, can prevent the fiber felt from absorbing water, allowing water to be discharged more quickly; although the treatment method in Example 2 reduces the separation rate because the microchannels in the fiber felt are occupied by water, making its separation rate lower than that of Example 1, it is still higher than that of Comparative Example 1. This is mainly because the untreated fiber felt in Comparative Example 1 has difficulty effectively separating water and oil, resulting in a very slow separation speed.

[0095] Comparative Examples 2-3

[0096] Comparative Examples 2 and 3 respectively provide a method for preparing an oil-water separation composite material. Compared with Example 1, the only difference is that step S2 is changed. The processing method of step S1 is completely the same as that of Example 1, and will not be described again here.

[0097] In Comparative Example 2, step S2 was omitted, and the treated high-performance fiber felt was used directly as the oil-water separation material. In Comparative Example 3, the corresponding fabrics were laminated onto the upper and lower surfaces without compression treatment.

[0098] The tests showed that when the oil-water separation material provided in Comparative Example 2 was used to separate the oil and water mixture, the separation rate was 0% and the oil-water separation efficiency was 0%. When the oil-water separation material provided in Comparative Example 3 was used to separate the oil and water mixture, the separation rate was 0% and the oil-water separation efficiency was 0%.

[0099] This shows that the compression process of the fiber felt during the tight wrapping of the polyester fabric is the key step in reducing the pore diameter of the fiber felt. The smaller the pore diameter, the stronger the wicking effect, and the better it can prevent the passage of oil, thus achieving the purpose of water and oil separation.

[0100] Comparative Example 4

[0101] Comparative Example 4 provides a method for preparing an oil-water separation composite material. Compared with Example 1, the only difference is that the specifications of the high-performance fiber felt in step S1 are changed. The remaining steps are completely consistent with Example 1 and will not be repeated here.

[0102] In this comparative example, the high-performance fiber felt is also basalt fiber needle-punched felt, but its basis weight is 100g / m². 2 It has a thickness of 12m, a width of 50cm, and a porosity of 40%.

[0103] According to the test results, when using the oil-water separation material provided in Comparative Example 4 to separate the mixture of engine oil and water, the separation rate is approximately 70 mL / min and the oil-water separation efficiency is approximately 99%.

[0104] This shows that different thicknesses and porosities of fiber felt also affect the oil-water separation rate. Under the same processing technology and methods, the higher the porosity, the more capillary channels the fiber felt material can form after compression, resulting in a faster separation speed and a stronger ability to block oil, thus achieving better oil-water separation.

[0105] Comparative Example 5

[0106] Comparative Example 5 provides a method for preparing an oil-water separation composite material. Compared with Example 1, the only difference is that the specifications of the first fabric in step S2 are changed. All other steps are completely consistent with Example 1 and will not be repeated here.

[0107] In this comparative example, the first fabric is also a polyester woven fabric, but its warp yarn count is 50D and its weft yarn count is 50D; the thickness of the polyester fabric is 0.3mm and its weight is 50g / m². 2 .

[0108] According to the test results, when using the oil-water separation material provided in Comparative Example 5 to separate the mixture of engine oil and water, the separation rate is approximately 150 mL / min and the oil-water separation efficiency is approximately 65%.

[0109] This demonstrates that the yarn density of polyester fibers plays a crucial role in separation efficiency. Since the wicking effect of a fabric is closely related to its pore size, a higher yarn density creates more wicking channels, resulting in faster water film formation and effectively preventing oil from passing through the polyester fabric. The water film on the polyester fabric helps the material block the oil, achieving excellent oil-water separation. However, if the polyester yarn density is too high, the water-oil mixture may pass through due to excessively large pores and incomplete water film formation. This prevents the effective blocking of the oil, leading to a decrease in oil-water separation efficiency.

[0110] Comparative Example 6

[0111] Comparative Example 6 provides a method for preparing an oil-water separation composite material. Compared with Example 1, the only difference is that the composition of the oleophilic and hydrophobic finishing agent in step S11 is changed. The remaining steps are completely consistent with Example 1 and will not be repeated here.

[0112] In this comparative example, the concentration of the hydrophobic agent in the oleophilic-hydrophobic finishing agent solution was also 6 g / 100 mL, and the concentration of the crosslinking agent was also 4 g / 100 mL, but the hydrophobic agent was methacrylamide and the crosslinking agent was trimethyl-1,6-hexamethylene diisocyanate.

[0113] According to the test results, when using the oil-water separation material provided in Comparative Example 6 to separate the mixture of engine oil and water, the separation rate is approximately 90 mL / min and the oil-water separation efficiency is approximately 97%.

[0114] This shows that the type of hydrophobic agent can affect but still has an effect on oil-water separation. The main reason is the effect of the treatment agent on water film formation and the formation of water-conducting pores. The oleophilic and hydrophobic finishing agent will form a thin film on the fiber felt, which can help to create water-conducting channels and increase the speed of water transport.

[0115] Comparative Example 7

[0116] Comparative Example 7 provides a method for preparing an oil-water separation composite material. Compared with Example 2, the only difference is that the composition of the hydrophilic and oleophobic finishing agent in step S11 is changed. The remaining steps are completely consistent with Example 2 and will not be repeated here.

[0117] In this comparative example, the concentration of the oleophobic agent in the hydrophilic and oleophobic finishing agent solution was also 6 g / 100 mL, but the oleophobic agent was an olefinic acid series hydrophilic monomer.

[0118] According to the test results, when using the oil-water separation material provided in Comparative Example 7 to separate the mixture of engine oil and water, the separation rate is approximately 46 mL / min and the oil-water separation efficiency is approximately 95%.

[0119] This shows that the type of hydrophilic and oleophobic agent mainly affects the separation speed, but still has good water-oil separation efficiency.

[0120] In summary, this invention provides an oil-water separation composite material, its preparation method, and its application. The preparation method of this oil-water separation composite material includes: subjecting a high-performance fiber felt to oleophilic-hydrophobic treatment or hydrophilic-oleophobic treatment to obtain a treated high-performance fiber felt; bonding a superhydrophilic functional fabric and an oleophobic functional fabric to the upper and lower surfaces of the treated high-performance fiber felt, respectively; and compressing the high-performance fiber felt with the fabrics on the upper and lower surfaces to obtain the oil-water separation composite material. Through the above method, the oil-water separation composite material prepared by this invention has a sandwich composite structure, consisting of a superhydrophilic functional fabric, a treated high-performance fiber felt, and an oleophobic functional fabric from top to bottom. This structure allows for efficient oil-water separation by utilizing the synergistic effect of the fabric structure of each layer and their affinity and repellency properties for water and oil. Furthermore, this oil-water separation composite material possesses extremely high mechanical properties, high-temperature resistance, and corrosion resistance, enabling it to adapt to various extreme environments. The oil-water separation process can be repeated, and it can be applied in automotive engines to recover and reuse filtered engine oil.

[0121] The above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention.

Claims

1. A method for preparing an oil-water separation composite material, characterized in that, Includes the following steps: S1. Perform oleophilic-hydrophobic treatment or hydrophilic-oleophobic treatment on the high-performance fiber felt to obtain the treated high-performance fiber felt. S2. A superhydrophilic functional fabric is laminated onto the upper surface of the treated high-performance fiber felt, and an oleophobic functional fabric is laminated onto the lower surface of the treated high-performance fiber felt. The superhydrophilic and oleophobic functional fabrics are then compressed onto the high-performance fiber felt to obtain an oil-water separation composite material. A sandwich composite structure is formed, consisting of a superhydrophilic functional fabric, the treated high-performance fiber felt, and an oleophobic functional fabric, arranged from top to bottom. The fabrics on the upper and lower surfaces tightly wrap the high-performance fiber felt. The thickness of the high-performance fiber felt is physically compressed by pressing from top to bottom, reducing it to 50% to 70% of its original thickness. The fiber felt thickness is then maintained in a compressed state by sealing the edges. The superhydrophilic functional fabric is obtained by hydrophilic treatment of the first fabric; the first fabric is a polyester woven fabric. The first fabric has a warp yarn count of 150~450D, a weft yarn count of 150~450D, a thickness of 0.1~2 mm, and a weight of 50~900 g / m². 2 ; The oleophobic functional fabric is obtained by treating a second fabric with an oleophobic coating. The second fabric is a polyester woven fabric. The second fabric has a warp yarn count of 150-450D, a weft yarn count of 150-450D, a thickness of 0.1-2 mm, and a weight of 50-900 g / m². 2 ; In step S1, the high-performance fiber felt is formed by needle punching high-performance fibers, wherein the high-performance fibers are one or more selected from glass fiber, quartz fiber, carbon fiber, basalt fiber, aluminosilicate fiber, polyimide fiber, aramid fiber, and polyphenylene sulfide fiber; the basis weight of the high-performance fiber felt is 100 g / m². 2 ~140 g / m 2 The thickness is 0.3~30 mm, the width is 5~100 cm, and the porosity is 50%~70%.

2. The method for preparing the oil-water separation composite material according to claim 1, characterized in that: In step S2, the hydrophilic treatment method includes: immersing the first fabric in a hydrophilic treatment solution for 1 to 30 minutes, taking it out and rolling it 1 to 5 times under a pressure range of 0.1 to 0.8 MPa, and then baking the rolled first fabric at 100 to 200°C for 1 to 120 minutes to obtain a superhydrophilic functional fabric.

3. The method for preparing the oil-water separation composite material according to claim 1, characterized in that: In step S2, the oleophobic treatment method includes: laying the second fabric flat, spraying a hydrophilic and oleophobic finishing agent evenly 1-10 times with a spray gun, and spraying air pressure of 0.05-2MPa; after spraying, baking the second fabric at 100-200℃ for 1-120 minutes to obtain an oleophobic functional fabric.

4. The method for preparing the oil-water separation composite material according to claim 1, characterized in that: In step S1, the method of oleophilic-hydrophobic or hydrophilic-oleophobic treatment includes: S11. Prepare a solution of oleophilic and hydrophobic finishing agent or a solution of hydrophilic and oleophobic finishing agent of a predetermined concentration; S12. The finishing agent solution prepared in step S11 is loaded into the high-performance fiber felt by impregnation or spraying. S13. Baking treatment is performed on the high-performance fiber felt loaded with finishing agent solution.

5. The method for preparing the oil-water separation composite material according to claim 4, characterized in that: In step S11, the oleophilic-hydrophobic finishing agent solution contains a hydrophobic agent and a crosslinking agent; the concentration of the hydrophobic agent is 0.5~30 g / 100mL, and the concentration of the crosslinking agent is 0.5~10 g / 100mL; The hydrophobic agent includes one or more of the following: 2-methylimidazolium cobalt salt, hexadecyltrimethoxysilane, polydimethylsiloxane, TiO2 nanoparticles, 3-aminopropyltriethoxysilane, vinyltriethoxysilane, (3-chloropropyl)triethoxysilane, trifluoroethyl acrylate, trifluoroethyl methacrylate, hexafluorobutyl methacrylate, methacrylate, methacrylamide, isobornyl methacrylate, octadecylamine, triethoxyoctylsilane, and dodecyltrimethoxysilane. The crosslinking agent includes one or more of the following: silane coupling agent, toluene diisocyanate, diphenylmethane diisocyanate, naphthalene diisocyanate, terephthalic diisocyanate, dimethylbiphenyl diisocyanate, polymethylene polyphenyl isocyanate, 1,6-hexamethylene diisocyanate, trimethyl-1,6-hexamethylene diisocyanate, isophorone diisocyanate, 1,4-cyclohexane diisocyanate, dicyclohexylmethane diisocyanate, methylcyclohexyl isocyanate, cyclohexane dimethylene diisocyanate, norbornene dimethylene isocyanate, HDI trimer, and IPDI trimer.

6. The method for preparing the oil-water separation composite material according to claim 4, characterized in that: In step S11, the hydrophilic oleophobic finishing agent solution contains an oleophobic agent, and the concentration of the oleophobic agent in the hydrophilic oleophobic finishing agent solution is 0.5~30g / 100mL; The oleophobic agent includes one or more of the following: fluoroacrylate polymer treatment agent, nano and micron-sized organosilicon filler, hydroxyl-containing fluorinated polyether, fluorocarbon alcohol, hydroxyl silicone oil, octadecyl alcohol, amino-containing fluorinated polyether, amino fluorocarbon, amino silicone oil, octadecylamine, methoxyfluorosilane, ethoxyfluorosilane, propoxyfluorosilane, perfluoroalkyl trichlorosilane, fluoroisocyanate, silicone isocyanate, octadecyl isocyanate, and dodecafluoroheptyl methacrylate.

7. The method for preparing the oil-water separation composite material according to claim 4, characterized in that: In step S13, the baking temperature is 100~200℃ and the baking time is 1~120min.

8. An oil-water separation composite material, characterized in that: The oil-water separation composite material is prepared by the preparation method described in any one of claims 1 to 7, comprising a high-performance fiber felt treated with oleophilic-hydrophobic or hydrophilic-oleophobic methods, a superhydrophilic functional fabric disposed on the upper surface of the high-performance fiber felt, and an oleophobic functional fabric disposed on the lower surface of the high-performance fiber felt.

9. The application of the oil-water separation composite material according to claim 8 in the field of automobile engines.

Citation Information

Patent Citations

  • Oil-water separation fabric as well as preparation and application thereof

    CN109680502A

  • Oil-water separation method based on hydrophilic oleophobic fabric

    CN112169376A

  • Composite for oil-water separation, synthesis methods and applications of same

    US20180243666A1